2020
DOI: 10.21203/rs.3.rs-52460/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Presence and strength of binding of IgM, IgG and IgA antibodies against SARS-CoV-2 during CoViD-19 infection

Abstract: Surface Plasmon Resonance imaging (SPRi) was used to determine the presence and strength of binding of IgG, IgM and IgA against the Receptor Binding Domain (RBD) of SARS-CoV-2 in sera of 119 CoViD-19 patients. The high-throughput assay enables to follow the specific immune response of ultimate 384 individuals for these four parameters in one run. The measured IgG, IgM and IgA levels correlated with ELISA (Euroimmun: Anti-SARS-CoV-2, IgG assay, r-0.95, ECLIA: Anti-SARS-CoV-2 Ig electrochemiluminescence r=0.73).… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…SPR sensing is thus well suited for quantitative analysis of SARS-CoV-2 proteinprotein 35,36 or protein-antibody 37,38 interactions, detecting SARS-CoV-2 RNA 39,40 or sensing antibodies associated to SARS-CoV-2 41,42 . A recent study showed that the use of SPR imaging can be used to detect antibody isotypes in sera of clinical patients 43 , paving the way for the use of SPR in clinical investigations. That initial study focused on the detection of antibodies only for the spike protein on an instrument confined to a centralized laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…SPR sensing is thus well suited for quantitative analysis of SARS-CoV-2 proteinprotein 35,36 or protein-antibody 37,38 interactions, detecting SARS-CoV-2 RNA 39,40 or sensing antibodies associated to SARS-CoV-2 41,42 . A recent study showed that the use of SPR imaging can be used to detect antibody isotypes in sera of clinical patients 43 , paving the way for the use of SPR in clinical investigations. That initial study focused on the detection of antibodies only for the spike protein on an instrument confined to a centralized laboratory.…”
Section: Introductionmentioning
confidence: 99%